Hamartigenia, de Aurélio Prudêncio Clemente: comentário, tradução e notas - Renato Felipe de Oliveira Romano (2017)
The objective of this work was to present a translation to Portuguese of the poem Hamartigenia by Aurelius Prudentius Clemens (348-c.405 AD). Philosophical and explanatory notes were added, as well as commentaries on the poems basic themes, namely: the unity of God, the heresy of Marcion, the origin of sin, the demon as author and instigator of evil, Creation prior to and after the Fall of man, the vices and destiny of the human soul. In the field of comparative literature, one also analyzed the poems literary and biblical sources, as well as the echo of ancient pagan and Christian writers, in order to clarify how Prudentius inserts himself into the Latin poetry tradition. Considering the fact that Prudentius poem may be classified as Latin didactic poetry, this work discussed not only the main characteristics of this genre, but also the pastoral, epic and satiric elements of the poem.